Benefits of ozonation before activated carbon adsorption for the removal of organic micropollutants from wastewater effluents. (April 2020) - Guillossou, Ronan; Le Roux, Julien; Brosillon, Stéphan; Mailler, Romain; Vulliet, Emmanuelle; Morlay, Catherine; Nauleau, Fabrice; Rocher, Vincent; Gaspéri, Johnny
Abstract: Advanced processes for the removal of organic micropollutants (OMPs) from wastewater effluents include adsorption onto activated carbon, ozonation, or a combination of both processes. The removal of 28 OMPs present in a real wastewater effluent was studied by ozonation coupled to activated carbon adsorption and compared to a sole adsorption. The influence of the specific ozone dose (0.09–1.29 gO3 /gDOC) and the influence of the powdered activated carbon (PAC) dose (2, 5 and 10 mg/L) were first studied separately. OMPs removal increased with both the specific ozone dose (up to 80% for a dose higher than 0.60 gO3 /gDOC) and the PAC dose. Ozonation performances decreased in presence of suspended solids, which were converted to dissolved organic carbon. A correction of the specific ozone dose according to the suspended solids levels, in addition to nitrite, should be considered. The influence of ozonation (0.09, 0.22, 0.94 and 1.29 gO3 /gDOC) on OMPs adsorption was then assessed. OMPs adsorption didn't change at low specific ozone doses but increased at higher specific ozone doses due to a decrease in DOM adsorption and competition with OMPs. At low ozone doses followed by adsorption (0.22 gO3 /gDOC and 10 mg/L PAC), the two processes appeared complementary as OMPs with a low reactivity toward ozone were well absorbed onto PAC while most OMPs refractory to adsorption were well eliminated by ozone. Improved removals were obtained for all compounds with these selected doses, reaching more than 80% removal for most OMPs while limiting the formation of bromate ion. Graphical abstract: Image 1 Highlights: OMPs adsorption increased after ozonation at high specific ozone doses only. Ozonation performances were impacted by the presence of TSS. Low specific ozone doses allowed the removal of OMPs refractory to adsorption. Non-reactive OMPs toward ozone were well adsorbed onto PAC. The best combination was 0.20–0.30 gO3 /gDOC and 10 mg/L PAC.